Opinion 2469: Galago demidoff Fischer, 1806 (currently Galagoides demidoff; Mammalia, Primates, Galagidae) and Lemur minutus Cuvier, 1797: neotypes not designated - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has declined to use its plenary power to rule on the validity of the specific names of Galago demidoff Fischer, 1806 and Macropus (Galago) demidovii, Fischer, 1808 or to designate neotypes for Galago demidoff Fischer, 1806 and Lemur minutus Cuvier, 1797. As a result, the specific name demidoff Fischer, 1806, as published in the original binomen Galago demidoff remains available from normal application of the Code, and the specific name demidovii Fischer, 1808, as published in the original binomen Macropus (Galago) demidovii remains an unjustified emendation. Neotypes for both Galago demidoff Fischer, 1806 and Lemur minutus Cuvier, 1797 can be designated without application to the Commission by meeting all conditions of Article 75.3 of the Code.